CUSTOMER SATISFACTION ANALYSIS OF SHARIA LAUNDRY PERFORMANCE IN SHARIA ECONOMIC PERSPECTIVE - Dwi Belia; Putri Amalia Zubaedah (Co-Value : Jurnal Ekonomi, Koperasi & Kewirausahaan, 2021)
Background: Sharia laundry is laundry which in its implementation uses sharia principles. Many factors affect the quality and operation of a business in the service sector, thereby affecting customer satisfaction or service users. Laundry Syariah is an option to increase customer satisfaction. The purpose of the study: to determine the customer satisfaction of sharia laundry from an Islamic economic perspective, differences in sharia laundry in terms of customer satisfaction, and the marketing strategy used by sharia laundry in increasing customer satisfaction from a sharia perspective. Research method: descriptive-analytical method. Sources of data used are primary data sources from data obtained by observing the place to be studied and other data which is the result of direct interviews from sources, namely Hijrah Laundry Syariah and in the form of collecting documentation from books, articles, journals, the internet and various other sources which are then analyzed through data reduction, data display, and verification to obtain. The results of the study: Hijrah Laundry Syariah is a sharia-based laundry service located in Cirebon City. This laundry service has been established since 2019. Located precisely on Jalan Raya Pamengkang No. 14 Mundu District, Cirebon Regency. Viewed from the perspective of sharia economics, customer satisfaction for Hijrah sharia laundry follows the values and principles of sharia economics, which in the perspective of sharia economics customer satisfaction can be seen from five influencing factors, namely product quality, price, service quality, emotional factors, costs, and easy access to the product. Conclusion: The results of this study conclude that Laundry Syariah guarantees customer satisfaction because of Islamic services and systems and ensures the welfare of managers and customers